(NrUSSKO(B-(NNEMECKIJ SLOWARX (B:s (NoKOLO (B40 000 (NSLOW (B/s - (NnIKONOWA(B, (No(B.(Nn(B.s ((NmOSKWA (B:s (Ngis (B,s, 1963)
(NbIBLIOGR(B.: (NS(B. 4 - 5s
Keywords: (NnEMECKIJ QZYKs; (NrUSSKO(B-(NNEMECKIE SLOWARIs